Dynamic Facial Reanimation in an Overweight Patient and with Significant Comorbidities: An Objective Analysis of Labbè Technique - Horta, Ricardo; Frias, Francisca; Barreiro, Diogo; Gerós, Ana; Aguiar, Paulo (The Surgery Journal, 2021)
Gracilis free muscle transfer is considered the gold standard technique for facial reanimation in cases of facial palsy. However, it is limited by its long operative and recovery times, the need for a second surgical site, and its outcomes that can sometimes show midfacial bulk and oral commissure malposition. Facial reanimation with lengthening temporalis myoplasty (LTM)—Labbé technique— carries the advantage of having a shorter surgical time, a faster recovery, and being a less invasive surgery. Almost all patients included in studies of LTM were evaluated by subjective methods, and very little quantifiable data was available. A 64-year-old woman presented with long-standing incomplete right facial palsy secondary to acoustic neuroma surgery. Since she was overweight (body mass index [BMI]: 43.9) and had several cardiovascular comorbidities (hypertension, dyslipidemia), she was not a good candidate for gracilis free muscle transfer. She was submitted to facial reanimation with LTM. Fourteen months after surgery, she presented excellent facial symmetry, both at rest and in contraction, while smiling. She was evaluated with the Facegram-3D, a technology that we have developed for dynamic evaluation of facial muscle contraction. The analysis showed symmetry at rest and contraction, according to Terzis and Noah. Regarding vertical and horizontal displacement, the postoperative movement was synchronized and with less fluctuations when compared with the preoperative period. Notably, the anatomical pair's trajectories were smoother. Similar velocity profiles were found between anatomical pairs, with less abrupt changes in velocity values, further supporting improved movement control. Comparing the symmetry index, which takes a theoretical maximum of 1.0 for perfect 3D symmetry, its value was 0.56 for the commissures and 0.5 for the midpoints in the preoperative period, having improved to 0.91 and 0.82, respectively, 3 months postoperatively. Good aesthetic and functional results were achieved using the Labbè technique. LTM is a good option in cases of long-standing facial paralysis, if the patient desires a single-stage procedure with almost immediate dynamic function. Moreover, this technique assumes extreme importance in facial reanimation of patients of advanced age, overweight, or those who have several comorbidities.
Keywords: facial palsy; facial reanimation; labbè technique; overweight patient